Study Of The Optimization Of Measurenment Efficiency Model Of Fuzzy Data Envelopment Analysis - Desi Vinsensia; Yulia Utami; Awaluddin Fitra; Rina Nanda Hanifa; Mestriawan Barasa (Institute of Computer Science (IOCS), 2022)
The performance of determination efficiency is affected by both situation certainty and uncertainty. The goal of this study is to develop fuzzy data envelopment analysis models for measuring efficiency performance with the Data envelopment analysis (DEA) method and also a fuzzy method that considers the inputs and outputs of the decision making unit (DMU) on intuitionistic triangular fuzzy numbers. On model development, a step procedure in measurement efficiency performance is given. For processing its efficiency, there is input and output representation on useful intuitionistic triangular fuzzy numbers as output and input estimation data. The application of the fuzzy model to the given case demonstrates that it can be used and is capable of measuring efficiency performance performance more efficiently.